2004
DOI: 10.1016/j.forsciint.2004.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide intoxications in the Centre of Portugal: three years analysis

Abstract: Pesticides are used in most countries around the world to protect agricultural and horticultural crops against damage. Poisoning by these toxicant agents occurs as a result of misuse or accidental exposure, and also by oral ingestion (voluntary or not).In Portugal, pesticide intoxications are still a cause of death, found in a considerable number of cases. The authors retrospectively examined the cases of pesticide poisoning in the Centre of Portugal, from autopsies performed in the Forensic Pathology Service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
28
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 13 publications
9
28
0
1
Order By: Relevance
“…Quinalphos is frequently used in many countries and represents a source of toxicity to humans and vertebrate animals. A 3-year evaluation (2000)(2001)(2002) of forensic pesticide and herbicide intoxications in Portugal attributed about 29% of total cases to quinalphos (Teixeira et al, 2004).…”
Section: -Hydroxyquinoxaline (Hqo) Is the Main Metabolite Of Quinalpmentioning
confidence: 99%
“…Quinalphos is frequently used in many countries and represents a source of toxicity to humans and vertebrate animals. A 3-year evaluation (2000)(2001)(2002) of forensic pesticide and herbicide intoxications in Portugal attributed about 29% of total cases to quinalphos (Teixeira et al, 2004).…”
Section: -Hydroxyquinoxaline (Hqo) Is the Main Metabolite Of Quinalpmentioning
confidence: 99%
“…In 2011, 1.9% of total food samples analyzed in Europe exceeded the legal Maximum Residue Levels (MRL), while in Portugal that percentage rose to 3.1% of collected food samples (4.9% in fruits and nuts and 2.8% in vegetables) [4,5]. Intoxications caused by misuse or accidental exposure, and also by oral ingestion (voluntary or not) of organophosphorus compounds and herbicides were reported [6,7]. The reduction of the negative effects of intensive agriculture and pesticide use has been one of the major concerns of European policies [1,8].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that poisoning cases with pesticides have been considered to be important causes of morbidity and mortality in all parts of the world. [5][6][7][8][9][10] ATDs, as the first choice in the treatment of depressive illness, are becoming increasingly used due to the rapid growth in population of depression-affected people worldwide. [11][12][13][14] Meanwhile, the abuse of ATDs has become a significant problem in societies across the world because of their easy availability and toxicological effect.…”
Section: Introductionmentioning
confidence: 99%